Large-eddy simulation of the turbulent diffusion flame - Shumikhin, Andrey Aleksandrovich; Karpov, Aleksandr Ivanovich (Computational Continuum Mechanics, 2012)
A mathematical model of the subsonic unsteady turbulent flow of compressible reacting gas is presented. The model is based on the Large Eddy Simulation method and the integrated model of turbulent diffusion combustion. The general scheme of the computational algorithm is described. Calculations have been made to obtain the characteristics of turbulent diffusion flame in a cross flow of air. Critical conditions for fire extinction have been determined.